Distinct lesion morphology at 7-T MRI differentiates neuromyelitis optica from multiple sclerosis - Sinnecker, Tim; Jarius, Sven (Neurology, 2012)
Objective: To investigate distinct white matter and cortical gray matter pathology in neuromyelitis optica spectrum disorders (NMOSDs) and multiple sclerosis (MS) at 7-T MRI in a cross-sectional study. - Methods: We included 10 patients with NMOSDs and 18 patients with MS in our 7-T MRI study. The imaging protocol comprised T2*-weighted fast low angle shot and turbo inversion recovery magnitude sequences. White matter and cortical gray matter lesions were assessed with special regard to their (perivascular) localization as well as the expression of a hypointense rim. - Results: In total, we detected 140 white matter lesions in 7 of 10 patients with NMOSDs. In contrast to MS plaques, which were nearly exclusively centered by a small vein (92%) and showed a characteristic hypointense rim (23%), white matter changes in patients with NMOSDs were nonspecific in appearance and were only infrequently neighbored by a blood vessel (49 lesions [35%], p = 0.003). Hypointense rims were very rarely detectable (3 lesions [2%], p < 0.001). Cortical pathology was absent in NMOSDs. In our MS cohort, we detected 36 leukocortical, 8 intracortical, and 8 subpial cortical lesions in 7 of 18 patients. - Conclusion: The MRI features of white matter and the absence of cortical gray matter findings substantially differentiate NMOSDs from MS and can be used as a potential marker to distinguish these 2 entities. The fact that cortical pathology is common in MS but is not present in patients with NMOSDs may reflect the difference in the underlying pathogenesis.